Conversion of Olefins into Ketones by an Iron‐Catalyzed Wacker‐type Oxidation Using Oxygen as the Sole Oxidant1. Issue 5 (28th December 2017) - Puls, Florian; Knölker, Hans‐Joachim
Abstract: We describe a mild and operationally simple procedure for the oxidation of olefins into ketones. The reaction is catalyzed by the hexadecafluorinated iron–phthalocyanine complex FePcF16 with stoichiometric amounts of triethylsilane as an additive under oxygen atmosphere to give ketones in good to high yields with excellent chemoselectivity and functional group tolerance. Ketone formation proceeds in up to 95 % yield and with 100 % regioselectivity while the corresponding alcohols were observed as side products. Abstract : A greener process for the synthesis of ketones is based on the Wacker‐type oxidation of olefins with the hexadecafluorinated iron–phthalocyanine complex FePcF16 as the catalyst in the presence of triethylsilane and proceeds under oxygen atmosphere at room temperature. This reaction is operationally simple and can be conducted on gram scale.